Analisis Usabilitas Sistem Informasi Manajemen Puskesmas Depok II Menggunakan Metode Evaluasi Heuristik - Novrizal Fattah Fahmitra; Irving Vitra Paputungan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Puskesmas is the frontline institution in health services and counseling. In order to give the services usually Puskesmas has management information system (MIS) to support in data processing. The MIS that is used by them should be in top performance to ease the worker finds and work more effectively and efficiently. In order to ensure the MIS always performes, analysis must be conducted to find problems so improvement can be made. Using heuristic evaluation method, an evaluation is carried out based on 10 indicators by distributing questionnaires to the clinician at Puskesmas. Analysis shows that there are 8 problems from 4 heuristic indicators such as visibility of system status, comparison between the system and real world, flexibility and efficiency of use, help and documentation. The problems that were found are considerably small problems with small priority for improvements. Such problems can be use as references for improvements, enhancements and feature additions to the MIS in Puskesmas Depok II, Sleman District and to ease the user.